Influence Of Contact Pressure And Sliding Speed Dependence On The Tribological Characteristics Of An Activated Carbon Epoxy Composite Derived From Palm Kernel Under Dry Sliding Conditions - Abdollah, Mohd Fadzli; Mahmud, Dayang Nor Fatin; Masripan, Nor Azmmi; Tamaldin, Noreffendy; Amiruddin, Hilmi (Tsinghua University Press, 2019)
The objective of this work is to investigate the influence of contact pressure and sliding speed on the coefficient of friction and wear of an activated carbon-epoxy composite derived from palm kernel under dry sliding conditions. A wear mode map approach was employed to identify the transitions from mild to severe wear of the composite. The dry sliding test was executed by utilizing a ball-on-disc tribometer at different contact pressures and sliding speeds with a constant sliding distance and operating temperature. The results showed that, regardless of the sliding speed, the friction coefficient and wear rate of the composite increased drastically when a critical limit of contact pressure is exceeded. As for the sliding speed, both the friction coefficient and wear rate increased first and thereafter decreased at a higher speed of 500 rpm. A wear mode map is proposed to classify the boundary from mild to severe wear regimes. The predominant wear failures identified include micro-crack, fine grooves, debonding, delamination, debris, broken carbon, and fracture.